Commuting extensions of operators - Arlinsky, Yu. M.; Mogilevskii, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The maximal commuting proper extensions of a closed Hermitian operator and a dual pair of continuous operators in a Hilbert space are described; the criteria of their existence are established.